Optimizing DNA Extraction Methods from Leaf and Wood Tissues to Support Dipterocarp Conservation and Sustainable Forest Management - Arrofaha, Nawwall; Rachmat, Henti Hendalastuti; Dwiyanti, Fifi Gus; Adinugroho, Wahyu Catur; Siregar, Iskandar Zulkarnaen; Kamal, Irsyad; Syaputra, Dhika; Salamah, Andi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2026)
Dipterocarpaceae are economically important, contributing over 85% of Indonesia's timber exports. However, this crucial resource is increasingly threatened by illegal logging, habitat destruction, and the illegal timber trade, which jeopardize dipterocarp population. Furthermore, conservation efforts utilizing genetic and forensic techniques often encounter substantial challenges due to the complexities in DNA extraction protocol. To address this, the study aimed to enhance the efficiency of DNA extraction methodologies by comparing two methods: the modified cetyltrimethylammonium bromide (CTAB) and the Genomic DNA Mini Kit (Plant) from Geneaid Biotech Ltd. The research focused on leaf and wood samples from two species, spesifically Rubroshorea leprosula (Miq.) P.S.Ashton & J.Heck and Shorea laevis Ridl. For each of these species, five leaf and five wood samples were extracted using both methods. The quality of the DNA extraction was evaluated using electrophoresis and quantified with a Qubit fluorometer. Higher DNA concentrations were obtained with the modified CTAB method compared to the GeneAid kit for both R. leprosula and S. laevis, particularly in leaf tissue. The GeneAid kit consistently exhibited low DNA yield efficiency compared to the modified CTAB method for both species. Additionally, PCR amplification of both leaf and wood samples confirmed that the extracted DNA was suitable formolecular analyses. These findings not only contributed to laboratory applications but also served as practical tools for species identification and genetic conservation for sustainable forest management and law enforcement.